Food for thought? Experimental evidence on the learning impacts of a large-scale school feeding program - Aurino, Elisabetta; Gelli, Aulo; Adamba, Clement; Osei-Akoto, Isaac; Alderman, Harold (University of Wisconsin Press, 2023)
There is limited experimental evidence on the effects of large-scale, government-led interventions on human capital in resource-constrained settings. We report results from a randomized trial of the government of Ghana’s school feeding. After two years, the program led to moderate average increases in math and literacy standardized scores among pupils in treatment communities, and to larger achievement gains for girls and disadvantaged children and regions. Improvements in child schooling, cognition, and nutrition constituted suggestive impact mechanisms, especially for educationally-disadvantaged groups. The program combined equitable human capital accumulation with social protection, contributing to the “learning for all” sustainable development agenda.